Influence of the Target Molecule on the Orac Index - Lissi-Gervaso, E; Aspee-Lamas, A (American Chemical Society, 2012)
The ORAC (Oxygen Radical Absorbance Capacity) assay has been widely employed to evaluate the antioxidant ability of pure compounds, foods and beverages. The method usually employs fluorescein and AAPH (2,2 -Azo-bis(2- amidinopropane) dihydrochloride) as target molecule (TM) and peroxyl radical source, respectively. According to a simple competition between TM and additives (antioxidants) for peroxyl radicals, the ORAC values (relative to a reference antioxidant), should be independent on the TM employed. In the present work we present ORAC values obtained employing different TM, such as fluorescein, alizarin red, pyrogallol red and pyranine. The results clearly show that the ORAC index of pure compounds and complex samples strongly depends on the TM used. Contradictory results on the antioxidant capacity of herbal and tea infusions can be obtained if fluorescein and pyrogallol red ORAC assays are compared. The dependence of the ORAC index on the TM emphasize the role of secondary radical reactions on the ORAC derived indexes. © 2012 American Chemical Society.